Assessing sufficient capability: A new approach to economic evaluation. (August 2015) - Mitchell, Paul Mark; Roberts, Tracy E.; Barton, Pelham M.; Coast, Joanna
Abstract: Amartya Sen's capability approach has been discussed widely in the health economics discipline. Although measures have been developed to assess capability in economic evaluation, there has been much less attention paid to the decision rules that might be applied alongside. Here, new methods, drawing on the multidimensional poverty and health economics literature, are developed for conducting economic evaluation within the capability approach and focusing on an objective of achieving "sufficient capability". This objective more closely reflects the concern with equity that pervades the capability approach and the method has the advantage of retaining the longitudinal aspect of estimating outcome that is associated with quality-adjusted life years (QALYs), whilst also drawing on notions of shortfall associated with assessments of poverty. Economic evaluation from this perspective is illustrated in an osteoarthritis patient group undergoing joint replacement, with capability wellbeing assessed using ICECAP-O. Recommendations for taking the sufficient capability approach forward are provided. Highlights: Aligning health economics and multidimensional poverty methods to measure wellbeing. Sufficient capability offered as objective in line with capability theory. Years of Sufficient Capability developed to assess capability wellbeing over time. Illustration of the Years of Sufficient Capability method for decision making.